Mechanical Strength and Microstructure Properties of Concrete Incorporating Copper Slag as Fine Aggregate: A State-of-the-Art Review - Tareg Abdalla Abdalla; Turki S. Alahmari (Advances in Civil Engineering, 2024)
Incorporation solid waste generated in industry into concrete production is considered an environmentally sustainable approach as it reduces pollution, lowers energy consumption, and mitigates the depletion of natural resources. Copper slag (CS) is a residual material produced through the copper smelting process. The slag materials are kept in expansive landfills and consume substantial land space. The typical approaches for managing CS involve recycling, metal recovery, and the creation of additional value through the manufacturing of items, including but not limited to railroad ballast, abrasive tools, cutting tools, roofing granules, abrasive tiles, glass, asphalt surfaces, and foundations for road construction. This study aimed to evaluate the mechanical strength and microstructural properties of concrete, focusing on using CS as a substitute for fine aggregate. This review systematically analyzes its use in concrete production over the last two decades. For the review, data were collected from various publishers, which are peer-reviewed articles, and validated using databases like Scopus, Scimago journal and country rank (SJR), Web of Science, etc. This review concluded that the potential of utilizing CS as a workable alternative for fine aggregate is highly attractive, given its superior performance in mortar and concrete mixes when compared to mixes without CS.